1984
DOI: 10.1111/j.1365-2125.1984.tb02556.x
|View full text |Cite
|
Sign up to set email alerts
|

Flurbiprofen interaction with single doses of atenolol and propranolol.

Abstract: In patients with mild hypertension, flurbiprofen in a dose of 100 mg daily for 7 days attenuated the hypotensive effect of a single dose of propranolol 80 mg but not of atenolol 100 mg. The attenuation was not due to an effect on the pharmacokinetic profile of either propranolol or atenolol. An alternative explanation is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…This effect may be small and may not represent the maximal response but is quite clearly present on analysis of standing and post-exercise systolic pressures. These observations are consistent with other studies showing rapid hypotensive effects of single doses of propranolol (Galloway et al, 1976) and atenolol (Webster et al, 1984).…”
Section: Discussionsupporting
confidence: 93%
“…This effect may be small and may not represent the maximal response but is quite clearly present on analysis of standing and post-exercise systolic pressures. These observations are consistent with other studies showing rapid hypotensive effects of single doses of propranolol (Galloway et al, 1976) and atenolol (Webster et al, 1984).…”
Section: Discussionsupporting
confidence: 93%
“…Chalmers et al 1984;Mills et al 1982;Salvetti et al 1982a,b;Steiness & Waldorff 1982;Watkins et al 1980 -fig. 7;Wing et al 1981), but has also been reported with piroxicam (Pugliese et al 1984;Wong et al 1986), naproxen (Abate et al 1990;Chalmers et al 1984), ibuprofen (Radack et al 1987), flurbiprofen (Webster et al 1984) and tiaprofenic acid (Smith et al 1985), although not with sulindac or diclofenac (Stokes et al 1991). A wide variety of antihypertensive agents have been involved including diuretics, ~-blockers, angiotensin converting enzyme (ACE) inhibitors and vasodilators.…”
Section: Nsaids Affecting Other Drugsmentioning
confidence: 89%
“…As both classes of drugs reduce PRA, pre-ß-blocker administration of NSAIDs may limit the antihy pertensive component related to PRA lowering. The blunting of the antihypertensive effect has not been ob served uniformly in all studies [24,29,30,32], The differ ences in some of the results between nonselective and selective beta blockers may be due to the fact that inhibi tion of prostaglandin synthesis might result in increased adrenoceptor sensitivity. Enhancement of alpha-medi ated vascular tone by NSAIDs might, therefore, be more apparent in the presence of a nonselective beta blocker than in the presence of a highly cardioselective one.…”
Section: Beta Blockersmentioning
confidence: 99%
“…Several studies have documented a blunting of antihy pertensive effects of beta blockers by NSAIDs [11,23,25,[27][28][29][30][31][32], the most common NSAID being indomethacin [11,23,25,27,30,31]. The variety of interactions between members of the different classes can be observed in table 3.…”
Section: Beta Blockersmentioning
confidence: 99%